Quadrivalent Live-Attenuated Influenza Vaccine in Milan preschools: an Italian experience of school-located flu vaccination within the 2022-2023 season - Stefania Roncaglia; Antonella Amendola; Paola Baldassarre; Francesca Barilli; Silvia Bianchi; Andrea Biuso; Claudia Chillemi; Clara Fappani; Chiara Gasparini; Maria Gori; Gabriella Guida; Francesca Ripoli; et al. (BMC, 2024)
Abstract Background In Italy, since the 2020-2021 flu season, the flu vaccine recommendation was extended to all children aged 6 months to 6 years and quadrivalent Live-Attenuated Influenza Vaccine (qLAIV) was introduced. Since school-aged children are important carriers of annual influenza epidemics, a school-based influenza vaccination program may potentially increase vaccine uptake. Recent studies, conducted in the UK and the US, show that school-based vaccination can reach higher percentage of paediatric vaccination coverage compared to children vaccinated in other settings. Methods During 2022-2023 flu season in 9 preschools located in Milan healthcare personnel vaccinated children with qLAIV at the end of a school day. A Google Form questionnaire was administered to preschoolers' parents of all preschools within the Municipality of Milan. Results In the preschools engaged in the vaccination program, 233 out of 1939 children were vaccinated (12%). Among these, 61 (26.2%) had never been vaccinated for influenza before. Vaccination coverage was 11.5% for Italian children and 14.3% for children coming from an immigrant background. We collected 3659 questionnaire responses, divided according to study participation status (371 from preschools that participated in the vaccination program and 3288 from other preschools in Milan). 57% of the families who answered to the questionnaire vaccinated their children for flu. qLAIV accounted for 85.6% of vaccinations. We observed a statistically significant difference in the percentage of vaccinated children between those attending a school participating in the project (67.9%) and children attending other schools (56%) (p < 0.001). Vaccination was administered by family pediatricians (48.9%), in vaccination centers (34.8%), in vaccine hubs (11.3%), in schools (2.6%), by private pediatricians (1.6%) and in other settings (0.7%). Focusing on the responses from families whose children attend schools participating in the vaccination program, 21.8% stated that the vaccination was provided in school. Conclusion According to our experience, in Italy, at the moment, only the cooperation between health providers and alternative settings, including schools, may expand flu vaccination coverage. In particular, schools are to be considered a place to inform and reach out to families, useful to increase vaccination coverage.